EDGE2D-EIRENE simulations of the impact of poloidal flux expansion on the radiative divertor performance in JET. (August 2017) - Viola, B.; Calabró, G.; Jaervinen, A.E.; Lupelli, I.; Maviglia, F.; Wiesen, S.; Wischmeier, M.; Contributors, JET
Highlights: Radiative divertor operation in nitrogen seeded, high-triangularity JET H-mode plasmas with various levels of poloidal flux expansion in semi-horizontal configuration have been predicted with the multi-fluid code EDGE2D-EIRENE. Flux expansion modified equilibria are predicted to radiate more in the vicinity of the X-point and have an ionization front extending further in the SOL than the reference equilibrium. HFE cases offer a benefit in minimizing the nitrogen concentration needed for a given radiated power level. Simulations have also shown an effect of the recycling on the radiation: equilibria with lower recycling yield a lower radiation but at the moment, there are no indications on how to disentangle the effect of inner target recycling on the divertor radiation. Abstract: In the past at JET, with the MkI divertor, a systematic study of the influence of X-point height and poloidal flux expansion has been conducted[1, 2] showing minor differences in the radiation distribution, whereas in[3] experiment and simulations have shown enhancement of detachment as the flux expansion was increased. More recently at JET, equipped with the ITER-like wall (ILW), radiative seeded scenarios have been studied and a maximum radiation fraction 75% has been achieved. EDGE2D-EIRENE[4–6] simulations [7, 8] have already shown that the divertor heat fluxes can be reduced with N2 injection, qualitatively consistent with experimental observations[9], by adjusting the impurity injection rate to reproduce the measured divertor radiation. In this paper we will present edge predictive simulations on the assessment of effects of poloidal flux expansion and recycling on radiation distribution and X-point peaking on JET-ILW nitrogen seeded plasmas.